Music, emotion, and time perception: the influence of subjective emotional valence and arousal? - Droit-Volet, Sylvie (Frontiers Media S.A., 2013)
The present study used a temporal bisection task with short (<2 s) and long (>2 s) stimulus durations to investigate the effect on time estimation of several musical parameters associated with emotional changes in affective valence and arousal. In order to manipulate the positive and negative valence of music, Experiments 1 and 2 contrasted the effect of musical structure with pieces played normally and backwards, which were judged to be pleasant and unpleasant, respectively. This effect of valence was combined with a subjective arousal effect by changing the tempo of the musical pieces (fast vs. slow) (Experiment 1) or their instrumentation (orchestral vs. piano pieces). The musical pieces were indeed judged more arousing with a fast than with a slow tempo and with an orchestral than with a piano timbre. In Experiment 3, affective valence was also tested by contrasting the effect of tonal (pleasant) vs. atonal (unpleasant) versions of the same musical pieces. The results showed that the effect of tempo in music, associated with a subjective arousal effect, was the major factor that produced time distortions with time being judged longer for fast than for slow tempi. When the tempo was held constant, no significant effect of timbre on the time judgment was found although the orchestral music was judged to be more arousing than the piano music. Nevertheless, emotional valence did modulate the tempo effect on time perception, the pleasant music being judged shorter than the unpleasant music.